2008
DOI: 10.1002/agr.20174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of WASDE reports on implied volatility in corn and soybean markets

Abstract: This study investigates the impact of U.S. Department of Agriculture World Agricultural Supply and Demand Estimate (WASDE) reports on implied volatility in corn and soybean markets over 1985 to 2002. If WASDE reports resolve uncertainty, implied volatility should drop immediately after release of the reports. Results show that WASDE reports lead to a statistically significant reduction of implied volatility that averages 0.7 percentage points for corn and 0.8 percentage points for soybeans. The magnitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 26 publications
4
30
2
1
Order By: Relevance
“…In Model A (based on Equation ), estimated coefficients for both crop report variables are statistically distinguishable from zero, being positive for USDA and negative for CONAB. This indicates that the conditional variance would increase with the announcement of new USDA reports, which is consistent with previous work (Isengildina‐Massa et al, ,; Karali, ; Lehecka, ; McKenzie, ). On the other hand, CONAB reports appear to reduce the conditional variance of soybean returns.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In Model A (based on Equation ), estimated coefficients for both crop report variables are statistically distinguishable from zero, being positive for USDA and negative for CONAB. This indicates that the conditional variance would increase with the announcement of new USDA reports, which is consistent with previous work (Isengildina‐Massa et al, ,; Karali, ; Lehecka, ; McKenzie, ). On the other hand, CONAB reports appear to reduce the conditional variance of soybean returns.…”
Section: Resultssupporting
confidence: 91%
“…Results suggested no significant price reaction to the announcement of WASDE reports. Isengildina‐Massa et al () adopted a longer sample period (1985–2006) and event study framework, and found evidence that corn and soybean futures prices reacted to WASDE reports.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Price movements are larger following USDA reports (Isengildina, Irwin, and Good, 2006b). Similarly, Isengildina-Massa et al (2008a, 2008b) found that after WASDE reports containing NASS crop production reports were released, implied volatility in corn and soybean markets was reduced. Sumner and Mueller (1989) found that the harvest forecast reports released in the months of August, September, and October cause a greater change in corn and soybean market prices than other reports.…”
Section: Introductionmentioning
confidence: 97%
“…Those three papers, however, look at realized volatility rather than at volatility expectations. 3 Beside Adjemian et al (2016), we are aware of only one other paper on what moves implied volatilities in agricultural markets: Isengildina, Irwin, Good, & Gomez's (2008) event study of the impact of WASDE reports on corn and soybean implied volatility. 4 For agricultural markets see, for example, Fackler & King (1990) and Egelkraut, Garcia, & Sherrick (2007).…”
Section: Related Literaturementioning
confidence: 99%